Step-by-step explanation:
<u>Step 1: Solve using the first point</u>
<em>(2, 28)</em>
![28 = a(2)^3 + b(2)^2 + c(2) + d](https://tex.z-dn.net/?f=28%20%3D%20a%282%29%5E3%20%2B%20b%282%29%5E2%20%2B%20c%282%29%20%2B%20d)
![28 = 8a + 4b + 2c + d](https://tex.z-dn.net/?f=28%20%3D%208a%20%2B%204b%20%2B%202c%20%2B%20d)
<u>Step 2: Solve using the second point</u>
<em>(-1, -5)</em>
![-5 = a(-1)^3 + b(-1)^2 + c(-1) + d](https://tex.z-dn.net/?f=-5%20%3D%20a%28-1%29%5E3%20%2B%20b%28-1%29%5E2%20%2B%20c%28-1%29%20%2B%20d)
![-5 = -a + b - c + d](https://tex.z-dn.net/?f=-5%20%3D%20-a%20%2B%20b%20-%20c%20%2B%20d)
<u>Step 3: Solve using the third point</u>
<em>(4, 220)</em>
![220 = a(4)^3 + b(4)^2 + c(4) + d](https://tex.z-dn.net/?f=220%20%3D%20a%284%29%5E3%20%2B%20b%284%29%5E2%20%2B%20c%284%29%20%2B%20d)
![220 = 64a + 16b + 4c + d](https://tex.z-dn.net/?f=220%20%3D%2064a%20%2B%2016b%20%2B%204c%20%2B%20d)
<u>Step 4: Solve using the fourth point</u>
<em>(-2, -20)</em>
![-20 = a(-2)^3 + b(-2)^2 + c(-2) + d](https://tex.z-dn.net/?f=-20%20%3D%20a%28-2%29%5E3%20%2B%20b%28-2%29%5E2%20%2B%20c%28-2%29%20%2B%20d)
![-20 = -8a + 4b - 2c + d](https://tex.z-dn.net/?f=-20%20%3D%20-8a%20%2B%204b%20-%202c%20%2B%20d)
<u>Step 5: Combine the first and fourth equations</u>
<u />![28 - 20 = 8a - 8a + 4b + 4b + 2c - 2c + d + d](https://tex.z-dn.net/?f=28%20-%2020%20%3D%208a%20-%208a%20%2B%204b%20%2B%204b%20%2B%202c%20-%202c%20%2B%20d%20%2B%20d)
![8 = 8b + 2d](https://tex.z-dn.net/?f=8%20%3D%208b%20%2B%202d)
![8 - 8b = 8b - 8b + 2d](https://tex.z-dn.net/?f=8%20-%208b%20%3D%208b%20-%208b%20%2B%202d)
![(8 -8b)/2 = 2d/2](https://tex.z-dn.net/?f=%288%20-8b%29%2F2%20%3D%202d%2F2)
![4 - 4b = d](https://tex.z-dn.net/?f=4%20-%204b%20%3D%20d)
<u>Step 6: Solve for c in the second equation</u>
![-5 + 5 = -a + b - c + d + 5](https://tex.z-dn.net/?f=-5%20%2B%205%20%3D%20-a%20%2B%20b%20-%20c%20%2B%20d%20%2B%205)
![0 + c = -a + b - c + c + d + 5](https://tex.z-dn.net/?f=0%20%2B%20c%20%3D%20-a%20%2B%20b%20-%20c%20%2B%20c%20%2B%20d%20%2B%205)
![c = -a + b + d + 5](https://tex.z-dn.net/?f=c%20%3D%20-a%20%2B%20b%20%2B%20d%20%2B%205)
<u>Step 7: Substitute d with the stuff we got in step 5</u>
![c = -a + b + (4 - 4b) + 5](https://tex.z-dn.net/?f=c%20%3D%20-a%20%2B%20b%20%2B%20%284%20-%204b%29%20%2B%205)
![c = -a + b + 4 - 4b + 5](https://tex.z-dn.net/?f=c%20%3D%20-a%20%2B%20b%20%2B%204%20-%204b%20%2B%205)
![c = -a - 3b + 9](https://tex.z-dn.net/?f=c%20%3D%20-a%20-%203b%20%2B%209)
<u>Step 8: Substitute d and c into the first equation</u>
<u />![28 = 8a + 4b + 2(-a - 3b + 9) + (4 - 4b)](https://tex.z-dn.net/?f=28%20%3D%208a%20%2B%204b%20%2B%202%28-a%20-%203b%20%2B%209%29%20%2B%20%284%20-%204b%29)
![28 = 8a + 4b - 2a - 6b + 18 + 4 - 4b](https://tex.z-dn.net/?f=28%20%3D%208a%20%2B%204b%20-%202a%20-%206b%20%2B%2018%20%2B%204%20-%204b)
![28 - 22 = 6a - 6b + 22 - 22](https://tex.z-dn.net/?f=28%20-%2022%20%3D%206a%20-%206b%20%2B%2022%20-%2022)
![6 / 6 = (6a - 6b) / 6](https://tex.z-dn.net/?f=6%20%2F%206%20%3D%20%286a%20-%206b%29%20%2F%206)
![1 + b = a - b + b](https://tex.z-dn.net/?f=1%20%2B%20b%20%3D%20a%20-%20b%20%2B%20b)
![1 + b = a](https://tex.z-dn.net/?f=1%20%2B%20b%20%3D%20a)
<u>Step 9: Substitute a, b, and c into the third equation</u>
![220 = 64(1 + b) + 16b + 4(-(1 + b) - 3b + 9) + (4 - 4b)](https://tex.z-dn.net/?f=220%20%3D%2064%281%20%2B%20b%29%20%2B%2016b%20%2B%204%28-%281%20%2B%20b%29%20-%203b%20%2B%209%29%20%2B%20%284%20-%204b%29)
![220 = 64 + 64b + 16b + 4(-1 - b - 3b + 9) + 4 - 4b](https://tex.z-dn.net/?f=220%20%3D%2064%20%2B%2064b%20%2B%2016b%20%2B%204%28-1%20-%20b%20-%203b%20%2B%209%29%20%2B%204%20-%204b)
![220 - 100 = 60b + 100 - 100](https://tex.z-dn.net/?f=220%20-%20100%20%3D%2060b%20%2B%20100%20-%20100)
![120 / 60 = 60b / 60](https://tex.z-dn.net/?f=120%20%2F%2060%20%3D%2060b%20%2F%2060)
![2 = b](https://tex.z-dn.net/?f=2%20%3D%20b)
<u>Step 10: Find a using b = 2</u>
![a = b + 1](https://tex.z-dn.net/?f=a%20%3D%20b%20%2B%201)
![a = (2) + 1](https://tex.z-dn.net/?f=a%20%3D%20%282%29%20%2B%201)
![a = 3](https://tex.z-dn.net/?f=a%20%3D%203)
<u>Step 11: Find c using a = 3 and b = 2</u>
![c = -a - 3b + 9](https://tex.z-dn.net/?f=c%20%3D%20-a%20-%203b%20%2B%209)
![c = -(3) - 3(2) + 9](https://tex.z-dn.net/?f=c%20%3D%20-%283%29%20-%203%282%29%20%2B%209)
![c = -3 - 6 + 9](https://tex.z-dn.net/?f=c%20%3D%20-3%20-%206%20%2B%209)
![c = 0](https://tex.z-dn.net/?f=c%20%3D%200)
<u>Step 12: Find d using b = 2</u>
![d = 4 - 4b](https://tex.z-dn.net/?f=d%20%3D%204%20-%204b)
![d = 4 - 4(2)](https://tex.z-dn.net/?f=d%20%3D%204%20-%204%282%29)
![d = 4 - 8](https://tex.z-dn.net/?f=d%20%3D%204%20-%208)
![d = -4](https://tex.z-dn.net/?f=d%20%3D%20-4)
Answer: ![a = 3, b = 2, c = 0,d = -4](https://tex.z-dn.net/?f=a%20%3D%203%2C%20b%20%3D%202%2C%20c%20%3D%200%2Cd%20%3D%20-4)